Climate policy uncertainty, environmental regulation, and corporate green innovation - Yi, Dan; Hu, Jun; Yang, Jianlan (Frontiers in Environmental Science, 2025)
Green innovation is an important driver for enterprises to realize sustainable development, but there are “double externalities” of environmental protection and knowledge spillovers. The climate policy uncertainty is a “driver” for corporate green innovation, or a “barrier” hindering corporate green innovation. Existing literature has explored the relationship between the two based on specific industries, but no consistent conclusions have been reached. This article uses study employs data from 3,763 publicly listed companies in China from 2010 to 2020 as an empirical research sample to analyze examine the actual impact of climate policy uncertainty on corporate green innovation and its underlying mechanisms. It further examines the effects of climate policy uncertainty on different types of green innovation activities and the moderating effect of corporate social responsibility. The study finds that climate policy uncertainty can promote corporate green innovation, primarily through channels such as enhancing environmental regulation. Both corporate social responsibility and ESG performance have a positive moderating effect on the relationship between climate policy uncertainty and corporate green innovation. Heterogeneity analysis reveals that climate policy uncertainty can foster green innovation in state-owned enterprises, large enterprises, companies in eastern regions, and those in areas with lower levels of green finance development further research indicates that from the perspective of green innovation motivation, climate policy uncertainty promotes strategic green innovation but does not have a significant effect on substantive green innovation. The findings of this study provide a theoretical foundation and practical insights for the government in formulating relevant climate policies and promoting green innovation in enterprises.